The potential role of BCL-2 inhibition in amyloidosis and plasma cell leukemia - Alvanidis, Grigorios; Kotsos, Dimitrios; Frouzaki, Christina; Fola, Amalia; Hatjiharissi, Evdoxia (Frontiers in Oncology, 2025)
Plasma cell neoplasms include a spectrum of disorders, such as plasma cell leukemia (PCL) and light chain (AL) amyloidosis, all associated with poor prognosis and limited therapeutic options. Venetoclax is the first-in-class B-cell lymphoma 2 (BCL-2) inhibitor and triggers apoptosis selectively in cells reliant on the BCL-2 pathway for survival. Randomized clinical trials have established the anti-tumor activity and efficacy of venetoclax in selected patients with hematologic malignancies such as acute myeloid leukemia (AML), chronic lymphocytic leukemia (CLL), and multiple myeloma (MM). At the same time, recent studies suggest its potential application in rare plasma cell dyscrasias. Preliminary results from case reports and a small cohort of patients indicate that venetoclax may benefit patients with PCL. Regimens incorporating venetoclax have also demonstrated promising outcomes in patients with AL amyloidosis, particularly those with translocation (11;14). This review analyzes new data on venetoclax in AL amyloidosis and PCL and highlights the increasing significance of BCL-2 inhibition in plasma cell neoplasms beyond MM.